Playing is the Best Remedy Project: Pedagogical Relations Centered on the Children’s Cultural Productions - da Silva Mello, André; Rodrigues Galvão, Emmily; Helmer Trindade, Luísa; Lema Del Rio Martins, Rodrigo; Firmino Magalhães Barbosa, Raquel; Gomes de Assis Pimentel, Giuliano (Guará Journal, 2019)
The article aims at discussing pedagogical possibilities that acknowledge and value the autonomy and authorship of children under cancer treatment regarding games and fun activities offered by a Project in the field of cultural entertainment. To do so, it focuses the activities of the Playing is the Best Remedy Project (Projeto Brincar é o Melhor Remédio), developed through the partnership between the Learning Center with Children and their Duties (Núcleo de Aprendizagens com as Infâncias e seus Fazeres - NAIF), from the Physical Education and Sports Center, and the Capixaba Against Children’s Cancer Association (Associação Capixaba Contra o Câncer Infantil - ACACCI). It is about a collaborative research-action, which uses filed diary an photographic records as sources. The research subjects are 30 children, two Teachers and the Coordinator member of the Project. The analyses undertaken, in dialogue with Children’s Sociology and with Daily basis Studies, indicate that the reactive entry, combined with pedagogical processes centered on interaction and mediation, they favor the children’s autonomy and authorship regarding their relations with the fun activities and games offered by the Project.